Plio-Pleistocene Perth Basin water temperatures and Leeuwin Current dynamics (Indian Ocean) derived from oxygen and clumped-isotope paleothermometry - D. De Vleeschouwer; M. Peral; M. Marchegiano; A. Füllberg; N. Meinicke; H. Pälike; G. Auer; B. Petrick; C. Snoeck; S. Goderis; P. Claeys (Climate of the Past, 2022)
The Pliocene sedimentary record provides a window into Earth's climate dynamics under warmer-than-present boundary conditions. However, the Pliocene cannot be considered a stable warm climate that constitutes a solid baseline for middle-of-the-road future climate projections. The increasing availability of time-continuous sedimentary archives (e.g., marine sediment cores) reveals complex temporal and spatial patterns of Pliocene ocean and climate variability on astronomical timescales. The Perth Basin is particularly interesting in that respect because it remains unclear if and how the Leeuwin Current sustained the comparably wet Pliocene climate in Western Australia, as well as how it influenced Southern Hemisphere paleoclimate variability. To constrain Leeuwin Current dynamics in time and space, this project obtained eight clumped-isotope Δ 47 paleotemperatures and constructed a new orbitally resolved planktonic foraminifera ( Trilobatus sacculifer ) stable isotope record ( δ 18 O) for the Plio-Pleistocene (4–2 Ma) interval of International Ocean Discovery Program (IODP) Site U1459. These new data complement an existing TEX 86 record from the same site and similar planktonic isotope records from the Northern Carnarvon Basin (Ocean Drilling Program (ODP) Site 763 and IODP Site U1463). The comparison of TEX 86 and Δ 47 paleothermometers reveals that TEX 86 likely reflects sea surface temperatures (SSTs) with a seasonal warm bias (23.8–28.9 ∘ C), whereas T. sacculifer Δ 47 calcification temperatures probably echo mixed-layer temperatures at the studied Site U1459 (18.9–23.2 ∘ C). The isotopic δ 18 O gradient along a 19–29 ∘ S latitudinal transect, between 3.9 and 2.2 Ma, displays large variability, ranging between 0.5 ‰ and 2.0 ‰. We use the latitudinal δ 18 O gradient as a proxy for Leeuwin Current strength, with an inverse relationship between both. The new results challenge the interpretation that suggested a tectonic event in the Indonesian Throughflow as the cause for the rapid steepening of the isotopic ...